Anoikis resistance in diffuse glioma: The potential therapeutic targets in the future - Zhu, Zhengyang; Fang, Chaoyou; Xu, Houshi; Yuan, Ling; Du, Yichao; Ni, Yunjia; Xu, Yuanzhi; Shao, Anwen; Zhang, Anke; Lou, Meiqing (Frontiers in Oncology, 2022)
Glioma is the most common malignant intracranial tumor and exhibits diffuse metastasis and a high recurrence rate. The invasive property of glioma results from cell detachment. Anoikis is a special form of apoptosis that is activated upon cell detachment. Resistance to anoikis has proven to be a protumor factor. Therefore, it is suggested that anoikis resistance commonly occurs in glioma and promotes diffuse invasion. Several factors, such as integrin, E-cadherin, EGFR, IGFR, Trk, TGF-β, the Hippo pathway, NF-κB, eEF-2 kinase, MOB2, hypoxia, acidosis, ROS, Hsp and protective autophagy, have been shown to induce anoikis resistance in glioma. In our present review, we aim to summarize the underlying mechanism of resistance and the therapeutic potential of these molecules.